Digital Activism in Contemporary Islamic Politics: A Critical Analysis of Social Media's Impact on Islamic Movements - Nibrosu Rohid; Rahma Sugihartati; Bagong Suyanto; Daniel Susilo; Afriul Zikri (MILRev: Metro Islamic Law Review, 2025)
This study explores the phenomenon of digital activism within the context of contemporary Islamic politics in Indonesia, focusing on the influence of social media on the dynamics of Islamic movements. Social media has emerged as a new space for political mobilization and religious discourse, enabling Islamic groups to expand their reach, enhance participation, and consolidate support. The study employs a qualitative approach with a critical analysis of the content, strategies, and impacts of social media use by various Islamic movements, ranging from moderate to conservative. The findings reveal that social media serves as a communication tool and a discursive space for shaping identities, conveying political narratives, and mobilizing collective action. On the other hand, the use of social media by Islamic movements also presents challenges, including polarization, misinformation, and the potential for radicalization. The research highlights that digital activism has reshaped the landscape of Islamic politics in Indonesia, with social media as a key catalyst for this transformation. However, its impact must be critically understood within broader social, political, and cultural contexts. These findings significantly contribute to studying Islamic politics and digital transformation in the modern era. The research expands academic literature on contemporary Islamic politics by analyzing the role of social media as a tool for political transformation within Islamic movements in Indonesia. This study offers a fresh perspective on the intersection of religion and digital technology, emphasizing how social media shapes political identity, mobilizes support, and influences public discourse and policy. Academically, this research contributes by providing a nuanced understanding of the digitalization of religious, political movements in a non-Western democratic context, enriching comparative studies on digital activism and political Islam.